Increasing The Capacity of Rural Communities in Peacefully Resolving Legal Conflicts Through Mediation Training (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
Efforts to resolve legal conflicts in villages through non-litigation channels are increasingly being eroded, along with the increase in legal conflict resolution through litigation channels. This condition shows the importance of strengthening the capacity of village communities in managing conflicts peacefully through non-litigation resolutions. Therefore, this community service program aims to increase the capacity of village communities in resolving legal conflicts through peaceful (non-litigation) approaches. The program is implemented through participatory counseling, simulation-based training, group discussions, and mentoring activities in Nglarangan Village, Kanor District, Bojonegoro Regency. Data was collected through observation and evaluation of participants. The results show a significant increase in participants' understanding of the urgency of peaceful legal conflict resolution, the mediation process, constructive communication, and conflict analysis. In addition, participants have improved their skills in facilitating dialogue and formulating mutually beneficial agreements. This program contributes to strengthening community-based conflict resolution and promoting sustainable social harmony.